1997
DOI: 10.1007/bf02477685
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of particle size and aluminium distribution to the para-selectivity of ZSM-5 type zeolites

Abstract: Para-seleefivity of ZSM-5 zeolites with similar bulk SiIAI ratio, but different particte size and surface A1 concentration has been investigated in toluene disproportionation. Results showed that enhanced para-selechvity is a consequence not only of the particle size but also of the external surface aluminium concentration in the particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The treatment also improves catalyst stability, because the active sites on the external surface are the loci of unwanted (bimolecular, such as coking) reactions. [30] Thermogravimetric analysis of the used catalysts in air indicates that sample HW contains about half the coke content of sample H, in agreement with lower deactivation rate of the former specimen ( Figure 7).…”
supporting
confidence: 74%
See 1 more Smart Citation
“…The treatment also improves catalyst stability, because the active sites on the external surface are the loci of unwanted (bimolecular, such as coking) reactions. [30] Thermogravimetric analysis of the used catalysts in air indicates that sample HW contains about half the coke content of sample H, in agreement with lower deactivation rate of the former specimen ( Figure 7).…”
supporting
confidence: 74%
“…The deactivation rate being slower for HW, it can reasonably be expected that the p ‐xylene yield would ultimately be higher for HW than for H. Since the acidity (Brønsted and Lewis) of the mesoporous surface of sample HW is reduced compared to sample H, the acidic washing of the desilicated zeolite clearly improves the para selectivity as the (monomolecular) shape‐selective reaction is favored in the internal microporous network. The treatment also improves catalyst stability, because the active sites on the external surface are the loci of unwanted (bimolecular, such as coking) reactions 30. Thermogravimetric analysis of the used catalysts in air indicates that sample HW contains about half the coke content of sample H, in agreement with lower deactivation rate of the former specimen (Figure 7).…”
Section: Resultsmentioning
confidence: 64%
“…In our previous work [13,14] we have shown that in isomerization of xylenes as well as in disproportionation of toluene the activity/selectivity of the catalysts based on ZSM-5 is significantly influenced by the particle properties (size, shape and aluminum distribution) of the ZSM-5 zeolite.…”
Section: Introductionmentioning
confidence: 99%